2007
DOI: 10.1016/j.engfailanal.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Residual stresses and fatigue performance

Abstract: Residual stresses are an inescapable consequence of manufacturing and fabrication processes, with magnitudes that are often a high proportion of the yield or proof strength. Despite this, their incorporation into life prediction is primarily handled through sweeping assumptions or conservative application of statistics. This can lead to highly conservative fatigue design methodologies or unforeseen failures under dynamic loading. The push from the desire for higher levels of materials performance, coupled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(98 citation statements)
references
References 10 publications
1
80
0
5
Order By: Relevance
“…The beneficial effect of shot peening is a result of coupling of the residual stresses and strain hardening [7] although the relative beneficial contributions of each are still controversial [13]. It has been reported that the beneficial effect of strain hardening is in increasing the initiation life since high dislocation densities in the cold worked region result in higher yield stresses [7,14] and thus lower plastic strain amplitudes under stress controlled cycling [15];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of shot peening is a result of coupling of the residual stresses and strain hardening [7] although the relative beneficial contributions of each are still controversial [13]. It has been reported that the beneficial effect of strain hardening is in increasing the initiation life since high dislocation densities in the cold worked region result in higher yield stresses [7,14] and thus lower plastic strain amplitudes under stress controlled cycling [15];…”
Section: Introductionmentioning
confidence: 99%
“…The presence of compressive residual stresses can increase both initiation and crack propagation lives as a result of a reduction in the effective applied tensile stress [13].…”
Section: Introductionmentioning
confidence: 99%
“…When 5053-H321 aluminium plates welded using double pass of FSW, using synchrotron radiation technique James etal. 7 was found that effect of fatiguebending loading, a significantly increase thepeak of tensile and compressiveresidual stress also translation of theresidual stress field to the tensile side. In spot welding, using neutron diffraction technique Suzuki et al 8 also found where a fatigue fracture occured, on the majority of residual stress near the center of weld.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, microstructural evolution during annealing also associated with developmentultrafinegrained structure. 7 which is more dense, so it can increase the hardness value. 4 and the resistance to deformation.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The presence of residual stresses in engineering components and structures significantly affect the fatigue behavior [2], strength [3], and dimensional stability [4]. Many studies have been conducted to investigate the effects of residual stress on the fatigue life of different materials [5][6][7]. The effects of residual stress and surface hardness on the fatigue life under different cutting conditions of 0.45%C steel were studied by Sasahara [8].…”
Section: Introductionmentioning
confidence: 99%